2008
DOI: 10.1111/j.1398-9995.2008.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of challenge test results by flour‐specific IgE and skin prick test in symptomatic bakers

Abstract: High concentrations of flour-specific IgE and clear SPT results in symptomatic bakers are good predictors for a positive challenge test. Challenge tests with flours may be avoided in strongly sensitized bakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 13 publications
0
33
2
10
Order By: Relevance
“…Several studies demonstrated that the IgE-mediated response is mainly associated with work-related symptoms in bakery workers. 31,32 In the current study, TLR4 ht1 [AT] appeared to multiply the risk of exhibiting work-related lower respiratory symptoms along with the specific IgE antibody to wheat flour in a synergistic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that the IgE-mediated response is mainly associated with work-related symptoms in bakery workers. 31,32 In the current study, TLR4 ht1 [AT] appeared to multiply the risk of exhibiting work-related lower respiratory symptoms along with the specific IgE antibody to wheat flour in a synergistic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Swoista próba prowokacyjna jest metodą referencyjną do oceny innych metod diagnostycznych [1][2][3], jednak może być przeprowadzona jedynie w wyspecjalizowanych jednostkach diagnostyczno-orzeczniczych. Wiąże się z ryzykiem wystąpienia ciężkich reakcji alergicznych, dlatego nie u wszystkich pacjentów można ją wykonać [4]. Istnieje więc potrzeba ulepszania metod diagnostyki zarówno in vitro (asIgE), jak i in vivo (PTS) oraz ocena ich przydatności w diagnostyce chorób alergicznych.…”
Section: Wstępunclassified
“…Nie otrzymano natomiast żadnego dodatniego oznaczenia przy użyciu odczynników firmy Phadia (tab. 4 Tabela 2. Charakterystyka grupy badanej -piekarzy i rolników z podejrzeniem zawodowej alergii dróg oddechowych -cd.…”
Section: Tabela 2 Charakterystyka Grupy Badanej -Piekarzy I Rolnikówunclassified
See 2 more Smart Citations